PHYSICAL BEHAVIOURS IN ADOLESCENTS THAT CONTRIBUTE TO OVERWEIGHT/OBESITY - Keya , Rino Tryanto; Widjaja, Nur Aisiyah; Noviyanti, Tausiyah Rohmah; Alexander, Yoppi Yeremia; Iitdrie, Iitdrie; Hermanto, Edi; Ardianah, Eva; Bahmid, Moh; Hanindita, Meta Herdiana; Irawan, Roedi (Media Gizi Indonesia, 2025)
Physical behaviours research in adolescents is still limiting in regard of overweight/obesity. Physical behaviour according to World Health Organization Global School Student Health Survey (WHO-GSHS) had four components namely physical activity, active transportation, physical education and sedentary behaviour showed inconsistent results investigating the obesity/overweight epidemic. The objective of this study is to examine the physical behaviour and metabolic components in overweight/obese adolescents. A cross-sectional study was conducted from September to October 2019 involving healthy obese adolescents with overweight/obesity in Sidoarjo and Surabaya. The statistical analysis was test of normality for interval/ratio variables, descriptive, bivariate correlation and binary logistic regression. All the analysis were conducted using SPSS ver. 21 (IBM, US). A total of 109 subjects were recruited in this study, consisting of male (50.46%) and female (49.54%) adolescents. The mean age of the subjects were 15.13 + 1.46 years old. Adolescents with sufficient physical activity, physical transport, physical class and recommended screen time was 93.58%, 23.85%, 14.68% and 36.70% respectively. The overweight subjects were 63 (57.80%) and obesity was 46 (42.20%), and prevalent in male than female (65.22% vs. 34.78%, p=0.012). The prevalent of MetS was 53.21%, no significant difference of MetS distribution among male and female (p=0.506). Subjects with physically transport behaviour had lower risk of abdominal obesity by 0.266-times than subjects with physically immobile. Thus, physical behaviour score did not correlate with anthropometric parameters indicating to overweight/obesity and metabolic factors, but the component of physical behaviour, especially sedentary lifestyle correlated with anthropometric parameters and systolic blood pressure.